2011
DOI: 10.1002/lt.22344
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for long-term mortality in a large cohort of patients wait-listed for liver transplantation in Brazil

Abstract: Liver donor shortage and long waiting times are observed in many liver transplant programs worldwide. The aim of this study was to evaluate the wait list in a developing country, before and after the introduction of the MELD scoring system. In addition, the MELD score ability to predict mortality in this setting was assessed. A single-center retrospective study of patients wait-listed for liver transplantation between 1997 and 2010 was undertaken. There were 1339 and 762 patients on the list in pre-MELD and ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Reasons for failure to receive transplantation have included lack of available organs, high expense, and the requirement for lifelong immunosuppressive medication. Other treatment strategies include bioartificial livers that are short of liver cells and medical management [ 2 ]. Consequently, there is an urgent need for novel therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for failure to receive transplantation have included lack of available organs, high expense, and the requirement for lifelong immunosuppressive medication. Other treatment strategies include bioartificial livers that are short of liver cells and medical management [ 2 ]. Consequently, there is an urgent need for novel therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…Besides medical management of organ dysfunction there are no specific approaches to treat patients with ACLF. The use of liver transplantation in this context is hampered by the shortage of organs5 as well as by the high frequency of concomitant conditions that contraindicate the procedure. The use of extracorporeal albumin dialysis by the molecular adsorbent recirculating system (MARS) has been shown to remove protein‐bound substances and decrease the plasma concentrations of bilirubin, ammonium, and creatinine in patients with ACLF.…”
mentioning
confidence: 99%
“…Recent studies have reported that hyponatremia is associated with a high mortality rate in various medical conditions (Baran and Hutchinson 1984;Tierney et al 1986;Gill et al 2006;Whelan et al 2009;Waikar et al 2009;Wald et al 2010). Hyponatremia is particularly prevalent in chronic liver disease and associated with a poor prognosis in patients with end stage liver disease waiting for a liver transplant (Angeli et al 2006;Kim et al 2008;Basto et al 2011). However, the impact of pre-transplantation hyponatremia on outcomes following liver transplantation is still controversial.…”
mentioning
confidence: 99%